BUSINESS PERFORMANCE OF WOMEN MSMEs IN SUKOHARJO: THE ROLE OF ATTITUTE TO MONEY AND INSTITUTIONAL SUPPORT - Heni Susilowati; Myra Andriana; Titin Hargyatni; Dewi Widyaningsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The role of women entrepreneurs is increasing in carrying out entrepreneurial activities. The purpose of this research is to determine the effect of Entrepreneurial Self-Efficacy (ESE) in mediating the relationship between Attitute of Money (AoM) and Institutional Support (IS) on Women's MSMEs. The research population is entrepreneurs at Sukoharjo, Central Java. The data collection is used a questionnaire approach with a Linkert Scale. The sample is selected based on the specified criteria, namely female entrepreneurs who are still active in the last year joining ICSB Sukoharjo. The data is processed using the help of smart PLS software version 4.0. The result showed that AoM and IS have a significant effect on ESE. While AoM does not have a significant effect on the women's business performance but IS has a significant effect on women's MSMEs. The role of ESE appears to be ineffective mediating between AoM and KINBIS at the 5% significance level but at the 10% level it is influential. Meanwhile, the role of ESE is indirectly able to mediate the influence of IS on KINBIS Keywords: Attitute of Money, Entrepreneurial Self-Efficacy, Institutional Support, Women’s SMEs Performance